HUMOROUS EFFECTS ON FLOUTING CONVERSATIONAL MAXIMS FOUND IN INDONESIAN DRAMA COMEDY: A STUDY OF HUMOR IN LANGUAGE - Detrianto, Bagus (PEOPLE: International Journal of Social Sciences, 2018)
Humor and language cannot be separated one another, because both of them are in one unity. Due to the fact that humor is one of the important aspects of communication through language in order to make communications more relaxed. Thus, to make the conversation become friendly, people sometimes make jokes one another during the conversations. Therefore, people often break the role of cooperative principles by flouting the maxims. This research aimed to observe and investigate the relation of humorous effects with Grice’s conversational maxims found in drama comedy Bajaj Bajuri Spesial Lebaran edition, which was broadcasted in Trans TV. In addition, the data was obtained from YouTube which was uploaded by MR WISE on April 5th, 2017 with the title “Bajaj Bajuri (Spesial Lebaran, Lebaran Maafkan). After collecting the data, the researcher did the analysis based on the theory which proposed by Grice (1975), then the researcher analysed the relationship between the humorous effects in this drama comedy and the flouting of conversational maxims. The result showed that there were some flouted maxims, but it did not lead the conversations into the end. In fact, it might make the conversation lively and friendly, sometimes the flouted maxims also caused the humorous effects.